PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK VIVO DI KOTA LUBUKLINGGAU (STUDI KASUS DI RATU 3G PONSEL) - Yuli Efrianti; Almusadad Almusadad (Jurnal Interprof, 2020)
This study aims to determine the Effect of Products and Promotions on VIVO Brand Smartphone Purchasing Decisions in Lubuklinggau City. This research is a type of quantitative research. The research sample was 40 people. In this study using primary and secondary data sources. The results of the study of Product Variables partially influenced the VIVO Brand Smartphone Purchase Decision variable in Lubuklinggau City, this was evidenced from the tcount greater than ttable, which was 5.871>2.021 and a significant level of sig = 0.10. Promotion variable partially influences the VIVO Brand Smartphone Purchase Decision variable in Lubuklinggau City, this is evidenced from the tcount greater than ttable, namely 3,441> 2,021 and a significant level of sig = 0.10. Product and Promotion variables simultaneously influence the VIVO Brand Smartphone Purchase Decision in Lubuklinggau City, this is evidenced from the fcount value = 56,853 greater than the ftabel value= 3.25 and theprobability (sig. 0,000) is smaller or less than 0.05.